Physical and social factors determining quality of life for veterans with lower-limb amputation(s): a systematic review. Issue 24 (19th November 2016) - Christensen, Jan; Ipsen, Thomas; Doherty, Patrick; Langberg, Henning
Abstract: Purpose: Most veterans live for many years after their war-related traumatic lower-limb amputation, which is why understanding which factors influence health-related quality of life (HRQoL) remains important to their long-term management. The objective of this study was to perform a review of the literature to summarize any evidence on the physical and social determinants for HRQoL in veterans with uni- or bilateral lower-limb amputation(s). Method: MEDLINE, EMBASE, PEDro, CINAHL, Scopus and Cochrane databases were searched systematically for eligible studies. Inclusion criteria were: traumatic lower-limb amputation(s), HRQoL outcome and veterans. Physical and social factors that influence HRQoL were extracted. Results: The literature search identified 2073 citations, leading to the inclusion of 10 studies in the systematic review. Physical activity level, sport participation, level of amputation, back pain, years of education, as well as duration and severity of phantom pain were found to be determining factors for HRQoL among veterans with lower-limb amputation. Conclusions: The identified physical and social determinants were similar to those found in civilian traumatic amputees. More high quality research designs, interventions and complex statistical analyses are warranted to identify the physical and social factors that influence the HRQoL of veteran amputees. Implications for Rehabilitation: Rehabilitation staff should promote physical activity and participation in sport among veterans with lower-limb amputation(s). Level of amputation, back pain severity, years of education, duration of phantom pain and severity of phantom pain have been found to be determining factors for HRQoL and should be taken into consideration when planning rehabilitation programs for veterans with lower-limb amputations.